2011
DOI: 10.3917/gs.135.0239
|View full text |Cite
|
Sign up to set email alerts
|

Les personnes âgées dans les territoires ruraux : une double opportunité pour la création d'activités et d'emplois de service

Abstract: La part des retraités dans la population française et européenne est croissante, et l’espace rural vieillit. Nous montrons que, en milieu rural, les retraités peuvent être à la fois des usagers et des acteurs à part entière de la société de services, constituant ainsi une véritable opportunité de développement et de création d’activités dans ce secteur. Le créateur d’activités de service s’inscrit en effet dans un territoire multiscalaire et évolutif, dans lequel les organismes d’accompagnement et les caractér… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Secondly, while digital health promotion could be a solution to engage and reach the rural populations [ 71 ], these areas are still characterized by poorer broadband access, which can limit the adoption of eHT [ 82 , 83 ]. Thirdly, rural populations tend to be older than urban ones [ 84 , 85 ]. Previous studies have indicated that older adults have more limited access to technology in general and, consequently, tend to possess poorer digital health literacy skills than younger age groups [ 86 - 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, while digital health promotion could be a solution to engage and reach the rural populations [ 71 ], these areas are still characterized by poorer broadband access, which can limit the adoption of eHT [ 82 , 83 ]. Thirdly, rural populations tend to be older than urban ones [ 84 , 85 ]. Previous studies have indicated that older adults have more limited access to technology in general and, consequently, tend to possess poorer digital health literacy skills than younger age groups [ 86 - 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…La part des plus de 55 ans dans ces territoires atteint entre 30,6 % et 33,1 % selon les zones, contre 25,4 % à l'échelle nationale (Sabau, Blasquiet-Revol et Lenain, 2010). Pour autant, le déclin démographique des campagnes, entamé dès la fin du 19 e siècle, semble stabilisé depuis la fin du dernier mouvement d 'exode rural (1945-1975) et il est partiellement compensé par des migrations de population qui s'effectuent des zones urbaines vers les territoires ruraux.…”
unclassified